Why organisational readiness is vital in the fight against insider threats. Issue 8 (August 2020) - Rodbert, Mark
Abstract : A chain is only as strong as its weakest link. It's a well-known phrase, but one that rings particularly true when considering a business's cyber security. In Securonix's 2019 Insider Threat Survey Report, 73% of organisations confirmed that insider attacks are becoming more frequent, and 59% said they think that privileged IT users pose the biggest insider security risk to organisations. 1 Insider threat is on the rise, and it's time for more companies to become aware of the risk they face and prepare correctly. The insider threat is on the rise, and it's time for more companies to become aware of the risk they face and prepare correctly. Organisational readiness is a factor that too many overlook in their pursuit of complete security. The right foundations need to be set before any business can produce a top-drawer security system. Once employees understand the importance of their role in protecting their company and buy into a secure culture, businesses can expect to reap the full benefits of the technology they're installing, argues Mark Rodbert of Idax Identity Analytics.